EVALUACIÓN NUTRICIONAL EN ESTUDIANTES DE LA ESCUELA DE CIENCIAS BIOLÓGICAS DE LA UNIVERSIDAD NACIONAL DE TRUJILLO, DICIEMBRE DEL 2018 – MARZO DEL 2019 - DELGADO CARRILLO, Karen Geraldine (2019)
The objective of this research was to evaluate the nutritional status of students of the School of Biological Sciences of the National University of Trujillo between December 2018 and March 2019, with a sample of 58 students from the different cycles of the School of Biological Sciences. Biological Sciences, out of a total population of 240 students, at that time enrolled. The students were tested for blood glucose, hemoglobin, waist-hip index (ICC), weight, height and body mass index (BMI) and, percentage of body fat, finally, a survey was conducted to be able Determine your physical activity. For the statistical analysis of the results, the Stat Grafic Software was used to obtain the comparisons of the averages of each anthropometric study, where the groups were separated by sex in order to make the comparison and be able to compare with the parameters established by WHO. the results obtained. It is concluded that 27% of the studied population was overweight. Key